Global wage report 2012/2013. Wages and equitable growth (Geneva, 2012)
"The 2012/13 edition looks at the macroeconomic effects of wages, and in particular at how current trends are linked to equitable growth. The gap between wage growth and labour productivity growth is widening, the difference between the top and bottom earners is increasing, and the labour income share is declining.